Predicting imminent risk for fracture in patients aged 50 or older with osteoporosis using US claims data. Issue 1 (December 2016) - Bonafede, M.; Shi, N.; Barron, R.; Li, X.; Crittenden, D.B.; Chandler, D.
Abstract Summary Patient characteristics contributing to imminent risk for fracture, defined as risk of near-term fracture within the next 12 to 24 months, have not been well defined. In patients without recent fracture, we identified factors predicting imminent risk for vertebral/nonvertebral fracture, including falls, age, comorbidities, and other potential fall risk factors. Purpose Several factors contribute to long-term fracture risk in patients with osteoporosis, including age, bone mineral density, and fracture history. Some patients may be at imminent risk for fracture, defined here as a risk of near-term fracture within 12–24 months. Many patient characteristics contributing to imminent risk for fracture have not been well defined. This case-control study used US commercial and Medicare supplemental insured data for women and men without recent fracture to identify factors associated with imminent risk for fracture. Methods Patients included were aged ≥50 with osteoporosis, had a vertebral or nonvertebral fracture claim (index date; fracture group) or no fracture claim (control group) from January 1, 2006, to September 30, 2012, continuously enrolled and without fracture in the 24 months before index. Potential risk factors during the period before fracture were assessed. Results Using data from 12 months before fracture, factors significantly associated with imminent risk for fracture were previous falls, older age, poorer health status, specific comorbidities (psychosis, Alzheimer's disease, central nervous system disease), and other fall risk factors (wheelchair use, psychoactive medication use, mobility impairment). Similar findings were observed with data from 24 months before fracture. Conclusions In patients with osteoporosis and no recent fracture, falls, older age, poorer health status, comorbidities, and other potential fall risk factors were predictive of imminent risk for fracture. Identification of factors associated with imminent risk for vertebral/nonvertebral fracture may help identify and risk stratify those patients most in need of immediate and appropriate treatment to decrease fracture risk.